PENGARUH LATIHAN KEKUATAN OTOT LENGAN TERHADAP KKEMAMPUAN RENANG GAYA DADA 25 METER PADA MAHASISWA JURUSAN PENDIDIKAN KEPELATIHAN FIKKM UNIMA - Lombok, Iriando J.; Tamunu, Doortje; Bacilius Sukadana; Mieke Mumekh (JURNAL ILMIAH KESEHATAN MANADO, 2024)
The formulation of the problem in this research is: What is the effect of arm muscle strength training on the ability to swim 25 meter breaststroke in students of the PKL FIKKM UNIMA Department? The aim of the research is: To determine the effect of arm muscle strength training on the ability to swim 25 meter breaststroke in students of the PKL FIKKM UNIMA Department. Research Hypothesis: There is an influence of arm muscle strength training on the ability to swim 25 meter breaststroke in students of the PKL Department of FIKKM UNIMA. The research method used is the experimental method. The population is all 20 male students of Class B Semester I Department of PKL FIKKM UNIMA. Because the population is small, a total of 20 people will be used as samples, divided into two groups of 10 people each in the control group. The research design uses: Pre-Test and Post-Test with Randomized Groups. Hypothesis testing uses statistical techniques with the t test. The results of calculations using t-test statistics obtained an observation t value of tob = 3.303. Meanwhile, from the table of critical values ​​t with a real level of a = 0.05; n_1+n_2-2 obtained a t table value of ttab = 2.101. This fact shows that the value tob = 3.303 > ttab = 2.101, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.